γδ T Cell Immunotherapy—A Review - Kobayashi, Hirohito (Pharmaceuticals (Basel), 2015)
Cancer immunotherapy utilizing Vγ9Vδ2 T cells has been developed over the past decade. A large number of clinical trials have been conducted on various types of solid tumors as well as hematological malignancies. Vγ9Vδ2 T cell-based immunotherapy can be classified into two categories based on the methods of activation and expansion of these cells. Although the in vivo expansion of Vγ9Vδ2 T cells by phosphoantigens or nitrogen-containing bisphosphonates (N-bis) has been translated to early-phase clinical trials, in which the safety of the treatment was confirmed, problems such as activation-induced Vγ9Vδ2 T cell anergy and a decrease in the number of peripheral blood Vγ9Vδ2 T cells after infusion of these stimulants have not yet been solved. In addition, it is difficult to ex vivo expand Vγ9Vδ2 T cells from advanced cancer patients with decreased initial numbers of peripheral blood Vγ9Vδ2 T cells. In this article, we review the clinical studies and reports targeting Vγ9Vδ2 T cells and discuss the development and improvement of Vγ9Vδ2 T cell-based cancer immunotherapy.